Method for preparing high-corrosion-resistance golden conductive conversion film on surface of ZK61 magnesium alloy
By performing degreasing, alkali corrosion, rare earth and gold conductive conversion film preparation and sealing treatment on ZK61 magnesium alloy, the serious galvanic corrosion problem during the heat treatment process is solved, and its corrosion resistance is significantly improved, especially on the conductive conversion film.
Patent Information
- Application Number
- CN202411682981.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-21
AI Technical Summary
ZK61 magnesium alloy is prone to Zr and Zn segregation during production and heat treatment, resulting in serious galvanic corrosion and poor corrosion resistance, which affects the integrity and corrosion resistance of the chemical conversion film. Especially for conductive conversion films with low contact resistance, it has worse corrosion resistance.
Degreasing and alkaline corrosion treatment were performed using degreasing agents and alkaline solutions. Then, rare earth conversion film and golden conductive conversion film were prepared respectively using rare earth conversion film conversion liquid and golden conductive conversion film conversion liquid, and finally closed treatment was carried out to improve corrosion resistance.
By removing Zr and Zn substances from the surface layer, protecting Mg elements, rare earth and gold conductive conversion films are prepared to form a high corrosion resistance conversion film layer, which significantly improves the corrosion resistance of ZK61 magnesium alloy, especially on conductive conversion films with low contact resistance.
Smart Images

Figure CN119663262A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesium alloy surface treatment, and in particular to a method for preparing a highly corrosion-resistant golden conductive conversion film on the surface of a ZK61 magnesium alloy. Background Art
[0002] As one of the lightest engineering structural materials, alloys have attracted much attention in recent years and are widely used in the fields of automobiles, rail transportation, aerospace, weapons and equipment, 3C electronics, etc. Among the many magnesium alloy grades, ZK6l magnesium alloy is more popular because of its good mechanical properties and thermal conductivity.
[0003] However, ZK61 magnesium alloy is prone to Zr and Zn segregation during the production and heat treatment process, resulting in severe galvanic corrosion and poor corrosion resistance. As a result, even during the preparation process of the chemical conversion film, its severe galvanic corrosion has a great impact on the integrity and corrosion resistance of the chemical conversion film, and its corrosion resistance is even worse for the conductive conversion film with lower contact resistance. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a highly corrosion-resistant golden conductive conversion film on the surface of a ZK61 magnesium alloy, aiming to solve the problem in the prior art that ZK61 magnesium alloy is prone to Zr and Zn segregation during production and heat treatment, resulting in severe galvanic corrosion and poor corrosion resistance; and further resulting in a technical problem that even during the preparation process of the chemical conversion film, the severe galvanic corrosion has a great impact on the integrity and corrosion resistance of the chemical conversion film, and the corrosion resistance of the conductive conversion film with a lower contact resistance is even worse.
[0005] To achieve the above object, the present invention adopts a method for preparing a highly corrosion-resistant gold conductive conversion film on the surface of a ZK61 magnesium alloy, comprising the following steps:
[0006] Step 1: First, select a ZK61 magnesium alloy with no impurities on the surface and perform degreasing treatment with a degreasing agent at 45-70°C for 3-5 minutes;
[0007] Step 2: The degreased ZK61 magnesium alloy is subjected to alkaline etching treatment at a temperature above 85° C. for 3-5 minutes using an alkaline solution;
[0008] Step 3: After the alkaline etching treatment, the ZK61 magnesium alloy is subjected to alkaline bright cleaning at a temperature above 85° C. for 10-15 minutes using a cleaning agent;
[0009] Step 4: using a rare earth conversion film conversion solution to prepare a rare earth conversion film on the ZK61 magnesium alloy after alkaline bright cleaning;
[0010] Step 5: Based on the rare earth conversion film, a golden conductive conversion film conversion liquid is used to further prepare a golden conductive conversion film on the ZK61 magnesium alloy;
[0011] Step 6: Using a sealing agent to seal the ZK61 magnesium alloy on which the gold conductive conversion film is prepared;
[0012] Step 7: After the sealed ZK61 magnesium alloy is dried, the performance test can be performed.
[0013] The degreasing agent in step 1 includes 5-10 g / L Na2CO3, 5-10 mL / L AEO-9, 10-15 mL / L OP-10 and 200-300 mL / L C2H5OH, and the balance is H2O.
[0014] Wherein, the alkaline solution in step 2 includes 100 g / L KOH and the balance is H2O.
[0015] Wherein, the cleaning agent in step three includes 30-50 mL / L H2O2, 10-15 g / L KOH, 10-20 g / L sodium citrate, 10-20 g / L potassium sodium alcoholate, 10-20 g / L EDTA·2Na and 10-20 g / L sodium lactate.
[0016] The rare earth conversion film conversion solution in step 4 includes 5-7 g / L La(NO3)3 and 10-15 mL / L H2O2, and triethanolamine is used to adjust the pH value to 8-9.
[0017] Among them, the golden conductive conversion film conversion liquid in step five includes 3-5g / L KMnO4, 5-8g / L sodium polyphosphate, 2-3g / L Na2WO4, 2-3g / L NaVO3, 2-3g / L Na2MoO4, 1-2g / L Na2SiO3·9H2O and 1-2g / L sodium glutamate, and NaOH and H3PO4 are used to adjust the pH value to 9-10.
[0018] Wherein, the blocking agent in step six includes 1% DJB-823 and 0.5-10mL / L KT-545;
[0019] The surface must be kept dry and free of moisture before sealing. The sealing process temperature is 60-70℃ and ultrasonic vibration is performed for 20-30s.
[0020] Among them, the performance tests of the ZK61 magnesium alloy after sealing treatment are carried out after drying, including appearance inspection, surface resistance test and corrosion resistance salt spray test.
[0021] The method for preparing a high corrosion resistance gold conductive conversion film on the surface of a ZK61 magnesium alloy of the present invention utilizes the two-phase property of Zr and Zn to dissolve the Zr and Zn substances on the surface in an oxidized state in a highly alkaline environment to achieve the purpose of removing these high potential phases. At the same time, the Mg element is protected in a highly alkaline oxidized state environment, and then a layer of rare earth conversion film is prepared in an alkaline oxidizing environment, followed by preparation of a gold conductive conversion film, and then sealing, drying, and testing to complete the preparation of a high corrosion resistance gold conductive conversion film on the surface of the ZK61 magnesium alloy. In this way, the problem that the ZK61 magnesium alloy is prone to Zr and Zn segregation during production and heat treatment in the prior art, resulting in severe galvanic corrosion and poor corrosion resistance, is solved; and further, even in the process of preparing the chemical conversion film, the severe galvanic corrosion has a great impact on the integrity and corrosion resistance of the chemical conversion film, and the corrosion resistance of the conductive conversion film with lower contact resistance is even worse.
[0022] The preparation of rare earth conversion film enables the use of rare earth elements to rationalize the structure of the conversion film layer in the next step of preparing the conductive conversion film, so that the conductive conversion film can obtain a structure with good functions.
[0023] The golden yellow conductive conversion film conversion solution of the present invention belongs to a medium-temperature oxidative electrolyte system. The surface of the ZK61 magnesium alloy with Zr and Zn removed still has galvanic corrosion. Under the action of this corrosion current, MnO4 - WO4 2- , VO3 - 、MoO4 2- The ions will move toward the positive electrode phase, so the remaining Zr, Zn and smaller Mg crystals will be oxidized and covered by their reduction products. At the same time, due to the presence of polyphosphate ions, they will react with MoO4 2- Forming heteropolyacids, on the other hand, it will react with Mg to form a local phosphide layer. - WO4 2- , VO3 - 、MoO4 2- The radii are different, so a dense conversion film layer of oxidation, phosphating and passivation is formed. Glutamic acid, as an amphoteric surfactant, reacts with SO4 2- Combined with filling in the current-intensive area, the electrochemical impedance of the film layer is further increased and the corrosion resistance is further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 The present invention is a flow chart of the steps of preparing a highly corrosion-resistant golden conductive conversion film on the surface of a ZK61 magnesium alloy.
[0026] Figure 2 It is a schematic diagram of the results of the 96h salt spray test of the ZK61 magnesium alloy of the present invention. DETAILED DESCRIPTION
[0027] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0028] See also Figure 1 and Figure 2 ,in Figure 1 The present invention is a flow chart of the steps of preparing a highly corrosion-resistant gold conductive conversion film on the surface of a ZK61 magnesium alloy. Figure 2 It is a schematic diagram of the results of the 96h salt spray test of the ZK61 magnesium alloy of the present invention.
[0029] The present invention provides a method for preparing a highly corrosion-resistant golden conductive conversion film on the surface of a ZK61 magnesium alloy, comprising the following steps:
[0030] Step 1: First, select a ZK61 magnesium alloy with no impurities on the surface and perform degreasing treatment with a degreasing agent at 45-70°C for 3-5 minutes;
[0031] Step 2: The degreased ZK61 magnesium alloy is subjected to alkaline etching treatment at a temperature above 85° C. for 3-5 minutes using an alkaline solution;
[0032] Step 3: After the alkaline etching treatment, the ZK61 magnesium alloy is subjected to alkaline bright cleaning at a temperature above 85° C. for 10-15 minutes using a cleaning agent;
[0033] Step 4: using a rare earth conversion film conversion solution to prepare a rare earth conversion film on the ZK61 magnesium alloy after alkaline bright cleaning;
[0034] Step 5: Based on the rare earth conversion film, a golden conductive conversion film conversion liquid is used to further prepare a golden conductive conversion film on the ZK61 magnesium alloy;
[0035] Step 6: Using a sealing agent to seal the ZK61 magnesium alloy on which the gold conductive conversion film is prepared;
[0036] Step 7: After the sealed ZK61 magnesium alloy is dried, the performance test can be performed.
[0037] The degreasing agent in step 1 includes 8 g / L Na2CO3, 5 mL / L AEO-9, 10 mL / L OP-10 and 200 mL / L C2H5OH, with the remainder being H2O.
[0038] Wherein, the alkaline solution in step 2 includes 100 g / L KOH and the balance is H2O.
[0039] Among them, the cleaning agent in step three includes 40mL / L H2O2, 10g / L KOH, 15g / L sodium citrate, 15g / L potassium sodium alcoholate, 15g / L EDTA·2Na and 17g / L sodium lactate.
[0040] The rare earth conversion film conversion solution in step 4 includes 5 g / L La(NO3)3 and 12 mL / L H2O2, and triethanolamine is used to adjust the pH value to 8-9.
[0041] Among them, the golden conductive conversion film conversion liquid in step five includes 3g / L KMnO4, 5g / L sodium polyphosphate, 2g / L Na2WO4, 2g / L NaVO3, 2g / L Na2MoO4, 1g / L Na2SiO3·9H2O and 1g / L sodium glutamate, and NaOH and H3PO4 are used to adjust the pH value to 9-10.
[0042] Wherein, the blocking agent in step six includes 1% DJB-823 and 1.5 mL / L KT-545;
[0043] The surface must be kept dry and free of moisture before sealing. The sealing process temperature is 60-70℃ and ultrasonic vibration is performed for 20-30s.
[0044] Among them, the performance tests of the ZK61 magnesium alloy after sealing treatment are carried out after drying, including appearance inspection, surface resistance test and corrosion resistance salt spray test.
[0045] Appearance inspection: A bright golden conversion film is formed on the surface of test piece A.
[0046] Surface resistance test:
[0047]
[0048] Corrosion resistance salt spray test: Salt spray 96h, see the result diagram Figure 2 .
[0049] The method for preparing a highly corrosion-resistant gold conductive conversion film on the surface of a ZK61 magnesium alloy according to the present embodiment utilizes the two-phase property of Zr and Zn to dissolve the Zr and Zn substances on the surface in an oxidized state in a highly alkaline environment to achieve the purpose of removing these high-potential phases. At the same time, the Mg element is protected in a highly alkaline oxidized state environment, and then a layer of rare earth conversion film is prepared in an alkaline oxidizing environment, followed by preparation of a gold conductive conversion film, and then sealing, drying, and testing to complete the preparation of a highly corrosion-resistant gold conductive conversion film on the surface of the ZK61 magnesium alloy. In this way, the problem that the ZK61 magnesium alloy is prone to Zr and Zn segregation during production and heat treatment in the prior art, resulting in severe galvanic corrosion and poor corrosion resistance, is solved; and even in the preparation process of the chemical conversion film, the integrity and corrosion resistance of the chemical conversion film are greatly affected due to its severe galvanic corrosion, and the corrosion resistance of the conductive conversion film with lower contact resistance is even worse.
[0050] The preparation of rare earth conversion film enables the use of rare earth elements to rationalize the structure of the conversion film layer in the next step of preparing the conductive conversion film, so that the conductive conversion film can obtain a structure with good functions.
[0051] The golden yellow conductive conversion film conversion solution of the present invention belongs to a medium-temperature oxidative electrolyte system. The surface of the ZK61 magnesium alloy with Zr and Zn removed still has galvanic corrosion. Under the action of this corrosion current, MnO4 - WO4 2- , VO3 - 、MoO4 2- The ions will move toward the positive electrode phase, so the remaining Zr, Zn and smaller Mg crystals will be oxidized and covered by their reduction products. At the same time, due to the presence of polyphosphate ions, they will react with MoO4 2- Forming heteropolyacids, on the other hand, it will react with Mg to form a local phosphide layer. - WO4 2- , VO3 - 、MoO4 2- The radii are different, so a dense conversion film layer of oxidation, phosphating and passivation is formed. Glutamic acid, as an amphoteric surfactant, reacts with SO4 2- Combined with filling in the current-intensive area, the electrochemical impedance of the film layer is further increased and the corrosion resistance is further improved.
[0052] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.
Claims
1. A method for preparing a highly corrosion-resistant gold conductive conversion film on the surface of a ZK61 magnesium alloy, characterized in that: The following steps are involved: Step 1: First, select a ZK61 magnesium alloy with no impurities on the surface and perform degreasing treatment with a degreasing agent at 45-70°C for 3-5 minutes; Step 2: The degreased ZK61 magnesium alloy is subjected to alkaline etching treatment at a temperature above 85° C. for 3-5 minutes using an alkaline solution; Step 3: After the alkaline etching treatment, the ZK61 magnesium alloy is subjected to alkaline bright cleaning at a temperature above 85° C. for 10-15 minutes using a cleaning agent; Step 4: using a rare earth conversion film conversion solution to prepare a rare earth conversion film on the ZK61 magnesium alloy after alkaline bright cleaning; Step 5: Based on the rare earth conversion film, a golden conductive conversion film conversion liquid is used to further prepare a golden conductive conversion film on the ZK61 magnesium alloy; Step 6: Using a sealing agent to seal the ZK61 magnesium alloy on which the gold conductive conversion film is prepared; Step 7: After the sealed ZK61 magnesium alloy is dried, the performance test can be performed.
2. The method for preparing a highly corrosion-resistant gold conductive conversion film on the surface of ZK61 magnesium alloy according to claim 1, characterized in that: The degreasing agent in step 1 includes 5-10 g / L Na2CO3, 5-10 mL / L AEO-9, 10-15 mL / L OP-10 and 200-300 mL / L C2H5OH, with the balance being H2O.
3. The method for preparing a highly corrosion-resistant gold conductive conversion film on the surface of ZK61 magnesium alloy according to claim 2, characterized in that: The alkaline solution in step 2 includes 100 g / L KOH and the balance is H2O.
4. The method for preparing a highly corrosion-resistant gold conductive conversion film on the surface of ZK61 magnesium alloy according to claim 3, characterized in that: The cleaning agent in step three includes 30-50 mL / L of H2O2, 10-15 g / L of KOH, 10-20 g / L of sodium citrate, 10-20 g / L of potassium sodium tartrate, 10-20 g / L of EDTA·2Na and 10-20 g / L of sodium lactate.
5. The method for preparing a highly corrosion-resistant gold conductive conversion film on the surface of a ZK61 magnesium alloy as claimed in claim 4, characterized in that: The rare earth conversion film conversion solution in step 4 includes 5-7 g / L La(NO3)3 and 10-15 mL / L H2O2, and triethanolamine is used to adjust the pH value to 8-9.
6. The method for preparing a highly corrosion-resistant gold conductive conversion film on the surface of ZK61 magnesium alloy according to claim 5, characterized in that: The golden conductive conversion film conversion liquid in step five includes 3-5g / L KMnO4, 5-8g / L sodium polyphosphate, 2-3g / L Na2WO4, 2-3g / L NaVO3, 2-3g / L Na2MoO4, 1-2g / L Na2SiO3·9H2O and 1-2g / L sodium glutamate, and NaOH and H3PO4 are used to adjust the pH value to 9-10.
7. The method for preparing a highly corrosion-resistant gold conductive conversion film on the surface of ZK61 magnesium alloy according to claim 6, characterized in that: The blocking agent in step six includes 1% DJB-823 and 0.5-10 mL / L KT-545; The surface must be kept dry and free of moisture before sealing. The sealing process temperature is 60-70℃ and ultrasonic vibration is performed for 20-30s.
8. The method for preparing a highly corrosion-resistant gold conductive conversion film on the surface of ZK61 magnesium alloy according to claim 7, characterized in that: After the sealed ZK61 magnesium alloy is dried, performance tests are carried out including appearance inspection, surface resistance test and corrosion resistance salt spray test.
Citation Information
Cited By
Alkaline conductive chemical oxidation treatment method commonly used for magnesium alloy
CN121228321A